(untitled) (World Conference on Social Sciences, Law and Public Policy, 2026)
This article analyzes the scientific school of Mirzo Ulugbek and its role in the development of astronomy and mathematics in Central Asia during the fifteenth century. The study examines the formation of the Samarkand scientific environment, the activity of Ulugbek’s madrasah and observatory, and the contribution of prominent scholars such as Qazizada Rumi, Ghiyath al-Din Jamshid al-Kashi, and Ali Qushchi. The article argues that Ulugbek’s scientific school was not only an educational institution, but also a research center where astronomical observations, mathematical calculations, and scientific discussions were systematically organized. The findings show that the scientific heritage created in Samarkand, especially the astronomical tables known as “Zij-i Jadid-i Guragani”, played an important role in the history of world science.